Viariasi Ukuran Sel Cosmarium spp. dan Euastrum spp. (Desmidiaceae, Charophyte) dari lingkungan akuatik sekitar Universitas Palangka Raya - Chaidir Adam (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2022)
Desmids (Desmidiaceae) is the family of green algae that characterized by cells that are shaped of two symmetrical semicells and it is estimated that there up to 12,000 species of Desmids. Cosmarium and Euastrum are two genera of Desmids that considered as the most representative taxa of this family. They are vary widely in size and shape of the cells. Based on the results of preliminary observations, in the aquatic enviroment around University of Palangka Raya is rich in microalgal diversity including Desmids. Cell size and shape are the most important points to be known to study the microalgae. This research is aimed to study the variety of cell size of Cosmarium spp. and Euastrum spp. from the aquatic environment around Palangka Raya. The results of this study show that the Cosmarium cells have the dimension of 17-80 μm long and 14-57 μm wide; Euastrum cells have the dimension of 24-89 μm long and 17-80 μm wide.